Improving the sensitivity of cochlear implant integrity testing by recording electrode voltages with surface electrodes - Grasmeder, Mary; Rogers, Katrine; Aydin, Ziya; Hough, Kate; Verschuur, Carl; Newman, Tracey (Frontiers in Audiology and Otology, 2024)
Introduction Identification of faults with the internal, implanted, part of a cochlear implant presents a challenge for the cochlear implant community. Advanced Bionics Ultra V1 devices are vulnerable to moisture ingress, a hard failure, resulting in reduced volume and clarity for the recipient. The manufacturer uses a trans-impedance test “Electrical Field Imaging” to identify faulty Ultra V1 devices but reports the sensitivity of the test to be only 70–90%. Methods In our clinic we performed Electrode Voltage measurements with surface electrodes and have compared the two tests. Electrical Field imaging and Electrode Voltage (EV) measurements were available for 65 devices. Surface electrodes were attached to the earlobes and forehead and potentials measured in three montages: ipsilateral earlobe and forehead, contralateral earlobe and forehead, and both earlobes; voltages were extracted and relative voltages across the array were calculated. Results Relative EV were compared for the two earlobes montage and fitted to a third order polynomial function. A new criterion for identifying faulty devices was derived, with a deviation of < 6% for individual electrodes for normally functioning devices or ≥6% for faulty devices. All devices which were normal according to the new criterion (N = 15) had a normal electrical field imaging test, whilst 17/50 devices which were abnormal had normal electrical field imaging and 33/50 which were abnormal had abnormal electrical field imaging. Discussion The REVs test was well-tolerated and carried out in a routine cochlear implant clinic. Together with test sensitivity and reliability this may make it a new routine assessment tool to aid in distinguishing hard and soft failures.